Improving intergroup relations - Stephan, Walter G.
This book is intended both as supplementary reading for courses and as a practical guidebook for individuals and programmes interested in reducing prejudice and improving intergroup relations. It provides the only comprehensive review and compilation of techniques for roving intergroup relations
Keywords: Group relations training; Intergroup relations; Group relations training -- United States; Intergroup relations -- United States